2016
DOI: 10.7498/aps.65.128504
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on oxide-based thin film transisitors

Abstract: Oxide semiconductor is regarded as one of most suitable active materials of thin-film transistors (TFTs) for driving organic light-emitting diodes because of its advantages of high mobility, low-temperature processing, good electrical uniformity, visible-light transparency, and low cost. Currently oxide TFTs have been successfully applied to the backplanes of the flat-panel displays. This review gives a comprehensive understanding of the development process of oxide TFTs. In the present article, we review the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 123 publications
0
2
1
Order By: Relevance
“…Generally, the transfer characteristics of a-IGZO TFT shift positively under the action of PBS, which is due to the negative charges trapping at the interface of a-IGZO/GI and/or into the GI. [12] However, the contrary results are observed in this study. Therefore, we propose that the dominant mechanism be due to the positive charges, which are repelled to the back-channel interface by a vertical electric field, trapping at the interface of a-IGZO/passivation and/or into the passivation.…”
Section: Resultscontrasting
confidence: 89%
See 1 more Smart Citation
“…Generally, the transfer characteristics of a-IGZO TFT shift positively under the action of PBS, which is due to the negative charges trapping at the interface of a-IGZO/GI and/or into the GI. [12] However, the contrary results are observed in this study. Therefore, we propose that the dominant mechanism be due to the positive charges, which are repelled to the back-channel interface by a vertical electric field, trapping at the interface of a-IGZO/passivation and/or into the passivation.…”
Section: Resultscontrasting
confidence: 89%
“…However, the ES structure carries with it an extra mask. [12] The EMMO TFT tactfully makes a tradeoff by elevating the S/D electrodes onto the passivation, and the passivation layer plays the role of an ES layer. Next, a heat-treatment in oxygen induces n + S/D regions, which cancels the requirement for an extension of the gate electrode to underlap the S/D electrode contacts.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the performance of the TFTs is affected by various factors, while the active channel layer material is critical to fabricate high-performance TFTs [5]. Transparent oxide semiconductors (TOSs) with high-effect mobility, low off current, wide optical band gap (3.5 eV), and low-temperature fabrication (<250 °C) are considered as promising candidates of TFTs [6][7][8]. Especially, since high field-effect mobility ZnO TFT prepared at room temperature has been reported by Fortunato and Martins et al in 2004 [9], ZnO-based TFTs have attracted the most attention.…”
Section: Introductionmentioning
confidence: 99%